Fibrinogen in the glioblastoma microenvironment contributes to the invasiveness of brain tumor‐initiating cells. (10th March 2021) - Dzikowski, Lauren; Mirzaei, Reza; Sarkar, Susobhan; Kumar, Mehul; Bose, Pinaki; Bellail, Anita; Hao, Chunhai; Yong, V. Wee
Abstract: Glioblastomas (GBMs) are highly aggressive, recurrent, and lethal brain tumors that are maintained via brain tumor‐initiating cells (BTICs). The aggressiveness of BTICs may be dependent on the extracellular matrix (ECM) molecules that are highly enriched within the GBM microenvironment. Here, we investigated the expression of ECM molecules in GBM patients by mining the transcriptomic databases and also staining human GBM specimens. RNA levels for fibronectin, brevican, versican, heparan sulfate proteoglycan 2 (HSPG2), and several laminins were high in GBMs compared to normal brain, and this was corroborated by immunohistochemistry. While fibrinogen transcript was at normal level in GBM, its protein immunoreactivity was prominent within GBM tissues. These ECM molecules in tumor specimens were in proximity to, and surrounding BTICs. In culture, fibronectin and pan‐laminin induced the adhesion of BTICs onto the plastic substratum. However, fibrinogen increased the size of the BTIC spheres by facilitating the adhesive property, motility, and invasiveness of BTICs. These features of elevated invasiveness were corroborated in resected GBM specimens by the close proximity of fibrinogen with matrix metalloproteinase (MMP)‐2 and‐9, which are proteases implicated in metastasis. Moreover, the effect of fibrinogen‐induced invasiveness was attenuated in BTICs where MMP‐2 and ‐9 have been inhibited with siRNAs or pharmacological inhibitors. Our results implicate fibrinogen in GBM as a mediator of the invasive properties of BTICs, and as a target for therapy to reduce BTIC tumorigenecity. Abstract : We implicate fibrinogen in glioblastoma as a mediator of the invasive properties of brain tumour initiating cells, and as a target for therapy to reduce tumorigenecity